Usefulness of QuantiFERON®-TB Gold test in psoriatic patients under treatment with tumour necrosis factor blockers. (February 2014) - Saraceno, Rosita; Specchio, Francesca; Chiricozzi, Andrea; Sarmati, Loredana; Amicosante, Massimo; Chimenti, Maria Sole; Chimenti, Sergio
<x xml:space="preserve">Abstract</x> Objective: Infliximab is a human/mouse chimeric anti-tumour necrosis factor (TNF)-α antibody that is effective in the management of psoriasis. Anti-TNF treatments may reactivate latent tuberculosis infection (LTBI); therefore, screening for LTBI is mandatory before starting any anti-TNF-α therapy. The aim of this study is to evaluate the usefulness of the QuantiFERON®-TB Gold (QFT-G) test in psoriatic patients under treatment with infliximab. Research design and methods: A retrospective study had been performed on patients affected by psoriasis who had been treated with infliximab from 2003 to 2012 at a single centre. Main outcomes measures: QFT-G was tested by a standard TB enzyme-linked immunosorbent assay, based on detection of interferon-γ release from sensitized leucocytes exposed to the synthetic Mycobacterium tuberculosis antigens at baseline and every 6 months until the end of treatment. Results: A total of 140 patients were included. At baseline, 7 QFT-G tests were positive and 133 tests were negative. Of the 133 patients, 11 (8%) who were negative at baseline became QFT-G test positive during treatment. Of those 11 patients, 5 had a reversion during treatment. Of the 133 patients, 122 (92%) who were negative at baseline remained negative. Conclusions: It was found that the development of positive QFT-G tests, observed in 8% treated with infliximab, was not associated with pulmonary or extra-pulmonary tuberculosis.